2010
DOI: 10.1021/ja103768r
|View full text |Cite
|
Sign up to set email alerts
|

‘Carbene Radicals’ in CoII(por)-Catalyzed Olefin Cyclopropanation

Abstract: The mechanism of cobalt(II)-porphyrin-mediated cyclopropanation of olefins with diazoesters was studied. The first step--reaction of cobalt(II)-porphyrin with ethyl diazoacetate (EDA)--was examined using EPR and ESI-MS techniques. EDA reacts with cobalt(II)-porphyrin to form a 1:1 Co(por)(CHCOOEt) adduct that exists as two isomers: the 'bridging carbene' C' in which the 'carbene' is bound to the metal and the pyrrolic nitrogen of the porphyrin that has a d(7) configuration on the metal, and the 'terminal carbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
243
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 317 publications
(266 citation statements)
references
References 93 publications
20
243
0
3
Order By: Relevance
“…The minimal correction term is a correction for the condensed phase (CP) reference volume (1 L mol −1 ) compared to the gas phase (GP) reference volume (24.5 L mol −1 ). This leads to an entropy correction term (SCP = SGP + Rln{1/24.5} for all species, affecting relative free energies (298 K) of all associative steps of −2.5 kcal mol −1 [39]. Larger correction terms of −6.0 kcal mol −1 have been suggested based on solid arguments [40,41].…”
Section: Methodsmentioning
confidence: 99%
“…The minimal correction term is a correction for the condensed phase (CP) reference volume (1 L mol −1 ) compared to the gas phase (GP) reference volume (24.5 L mol −1 ). This leads to an entropy correction term (SCP = SGP + Rln{1/24.5} for all species, affecting relative free energies (298 K) of all associative steps of −2.5 kcal mol −1 [39]. Larger correction terms of −6.0 kcal mol −1 have been suggested based on solid arguments [40,41].…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] The EPR, ESI-MS as well as DFT studies revealed that the cobalt(II)-porphyrin-mediated cyclopropanation of olefins with diazoesters proceeds via the formation of the Fischer-type radical carbene II followed by a stepwise radical addition of an olefin (1) and cyclization cascade toward the corresponding cyclopropanes 3 and 4 (Scheme 1). 17,18 The "terminal radical carbene species" II and the "bridging carbene species" III were proposed to exist as redox isomers and in dynamic equilibrium with each other, although the latter was determined to be thermodynamically somewhat more stable according to DFT calculations. 18 While the dynamic equilibrium between the species II and III is expected to prevent the formation of dimerization byproducts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…radical reactivity that is unusual for carbenes bound to other metal porphyrin complexes. 17,10 The nucleophilic character of the carbene radicals II enables cobalt(II) porphyrins to catalyze also the cyclopropanation of electron-deficient olefins such as methyl acrylate.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt coordination compounds in general have become popular for H 2 conversion research [4][5][6][7][8], alkene hydrogenation [9][10][11][12][13], controlled radical polymerisation [14][15][16][17][18][19] and carbene-and nitrene-transfer reactions [20][21][22][23][24]. Cobaltmediated hydroformylation is well-known and has been continuously reviewed [25][26][27].…”
Section: Introductionmentioning
confidence: 99%